Radiologic placement of Hickman catheters using intravenous sedation in pediatric patients under 20 kg. Issue 7 (18th February 2022) - Kim, Jin Hyeok; Jeon, Ung Bae; Jang, Joo Yeon; Kim, Yong-Woo; Hwang, Jae-Yeon; Lim, Young Tak; Yang, Eu Jeen
Abstract : Abstract: Surgeons generally perform Hickman catheter insertion in children under general anesthesia. At times, it is difficult to perform procedures with an anesthesiologist for an interventional radiologist. Several diagnostic and therapeutic procedures are efficiently and safely conducted using intravenous (IV) sedation in children with a pediatrician. This study aims to evaluate the efficacy and safety of radiologically placed Hickman catheters using IV sedation in children under 20 kg. Fifty-nine catheters were inserted in 45 children under IV sedation. With continuous monitoring of vital signs, IV midazolam and ketamine were slowly infused by a pediatrician. Mean age and body weights were 3.2 years and 15.2 kg, respectively. Acute leukemia was the most common disease for the procedure (72.9%). The location of the catheter tip was evaluated by measuring the height of the thoracic vertebra. Technical success rate was 100%, and IV sedation-related complications did not occur. The right internal jugular vein was accessed for 51 catheters (86.4%), and the mean procedure time was 21.5 minutes. The 2 vertebral body units below the carina were the cavoatrial junction on a fluoroscopy image. Mean catheter life was 285 days, and catheters were removed post-treatment (35.6%). During follow-up, complications occurred in 29 cases (1.72 per 1000 catheter-days). Catheter-related infections were suspected in 4 patients (6.8%), with 1 positive result. Radiological Hickman catheter placement in children under 20 kg using IV sedation by pediatricians is effective and safe, with minimal complications. The carina is a landmark to estimate the cavoatrial junction in pediatric patients.